A General Access Route to High‐Nuclearity, Metal‐Functionalized Molecular Vanadium Oxides. Issue 9 (17th January 2022) - Greiner, Simon; Hettig, Jan; Laws, Alec; Baumgärtner, Katharina; Bustos, Jenna; Pöppler, Ann‐Christin; Clark, Adam H.; Nyman, May; Streb, Carsten; Anjass, Montaha
Abstract: Molecular metal oxides are key materials in diverse fields like energy storage and conversion, molecular magnetism and as model systems for solid‐state metal oxides. To improve their performance and increase the variety of accessible motifs, new synthetic approaches are necessary. Herein, we report a universal, new precursor to access different metal‐functionalized polyoxovanadate (POV) clusters. The precursor is synthesized by a novel solid‐state thermal treatment procedure. Solution‐phase test reactions at room temperature and pressure show that reaction of the precursor with various metal nitrate salts gives access to a range of metal‐functionalized POVs. The first nitrate‐templated molecular calcium vanadate cluster is reported. We show that this precursor could open new access routes to POV components for molecular magnetism, energy technologies or catalysis. Abstract : Controlled thermal treatment of the common decavanadate cluster in the solid state yields a universal precursor for the synthesis of large, metal‐functionalized polyoxovanadates, as demonstrated for three examples.